Docetaxel and Doxorubicin Codelivery by Nanocarriers for Synergistic Treatment of Prostate Cancer - Li, Ke; Zhan, Wenhua; Chen, Yulong; Jha, Rajiv Kumar; Chen, Xueli (Frontiers in Pharmacology, 2019)
Combination chemotherapy has been proven to be an efficient strategy for the treatment of prostate cancer (PCA). However, the pharmacokinetic distinction between the relevant drugs is an insurmountable barrier to the realization of their synergistic use against cancer. To overcome the disadvantages of combination chemotherapy in the treatment of PCA, targeted nanoparticles (NPs), which can codeliver docetaxel (DOC) and doxorubicin (DOX) at optimal synergistic proportions, have been designed. In this study, the DOC and DOX codelivery nanoparticles (DDC NPs) were constructed by hyaluronic acid (HA) and cationic amphipathic starch (CSaSt) through a self-assembly process. Human PCA cell lines (PC-3, DU-145, and LNCap) and mouse models were then used for evaluation in vitro and in vivo, respectively, of delivery and antitumor effects. The DDC NPs were spherical with rough surfaces, and the size and zeta potential were 68.4 ± 7.1 nm and -22.8 ± 2.2 mV, respectively. The encapsulation efficiencies of DOC and DOX in the NPs were 96.1 ± 2.3% and 91.4 ± 3.7%, respectively, while the total drug loading was 9.1 ± 1.7%. Moreover, the ratio of DOC to DOX in the DDC NPs was approximately 1:400, which aligned with the optimal synergistic proportions of the drugs. The DDC NPs exhibited excellent loading capacities, performed sustained and enzymatic release, and were stable in PBS, medium, and serum. After investigations in vitro, the DDC NPs were as effective as the dual drug combination in terms of cytotoxicity, antimigration, and apoptosis. Internalization results indicated that the DDC NPs could effectively deliver and fully release the payloads into PCA cells, and the process was mediated by the ligand-receptor interaction of HA with the CD44 protein. Low toxicity in vivo was confirmed by acute toxicity and hemolytic assays. The distribution in vivo showed that DDC NPs could enhance the accumulation of drugs in tumors and decrease nonspecific accumulation in normal organs. More importantly, DDC NPs significantly promoted the curative effect of the DOC and DOX combination in the PCA cell xenograft mouse model, indicating that the drugs with NPs did indeed act synergistically. This study suggests that the DDC NPs possess noteworthy potential as prospects for the development of PCA clinical chemotherapy.